2016
DOI: 10.1515/teme-2016-0019
|View full text |Cite
|
Sign up to set email alerts
|

Surface heat transfer coefficient measurement by immersed temperature sensor and inverse modelling

Abstract: A transient surface heating or cooling process of a solid is considered. A procedure for the determination of surface temperature and surface heat flux density during such a process is presented using a submersed temperature sensor in the solid. From this measured temperature the surface temperature and surface heat flux density are calculated by inverse process modelling. This method is prone to errors since measurement errors are amplified in the inverse process modelling and can thus easily become unaccepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Especially for the high-performance cooling required Figure 10. Left: electrically insulated thermocouple in the metallic probe with a drilled hole, cooled surface is on top; right: ceramic (insulating) probe material with a moulded thermocouple; red dots denote the effective measuring position of the thermocouple, [18] black lines represent the distance from the surface in tenths of millimeters. Figure 9.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Especially for the high-performance cooling required Figure 10. Left: electrically insulated thermocouple in the metallic probe with a drilled hole, cooled surface is on top; right: ceramic (insulating) probe material with a moulded thermocouple; red dots denote the effective measuring position of the thermocouple, [18] black lines represent the distance from the surface in tenths of millimeters. Figure 9.…”
Section: Discussionmentioning
confidence: 99%
“…This can be achieved by adopting the sensor depth and the sampling rate to the cooling conditions and the sensor noise. [18] The following figures show results from the simulations of a cooling process corresponding to an average heat flux density of %500 kW m À2 . In Figure 9a, it is shown that how the measurement error can be reduced by placing the sensor closer to the surface and reducing the sensor noise level.…”
Section: Heat Flux Measurementmentioning
confidence: 99%
See 3 more Smart Citations